2021
DOI: 10.18844/cjes.v16i5.6333
|View full text |Cite
|
Sign up to set email alerts
|

Improving motivation and science process skills through a mobile laboratory-based learning model

Abstract: The COVID-19 pandemic has affected all sectors of life, including the education sector. Physics learning activities, especially practicum activities, which so far have been very dependent on laboratory space-based activities, are very disturbed. This study aims to develop students' motivation and science process skills (SPS) during the pandemic. The sample of this study was 3 groups consisting of 90 students from 2 universities in the province of Lampung, Indonesia. The data obtained were analysed using the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Findings by Usman et al [17] demonstrated that the virtual laboratory ensured the development of SPS in the same way or even better than the traditional laboratory, while Aththibby et al [18] provided a restrained approach for SPS development by using a mobile laboratory-based learning model in developing SPS and motivation. A lot of research on addressing SPS through distance learning emphasizes the use of technology, incorporating a laboratory approach, yet not all schools have the privilege of having access to modern technological breakthroughs and advancements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Findings by Usman et al [17] demonstrated that the virtual laboratory ensured the development of SPS in the same way or even better than the traditional laboratory, while Aththibby et al [18] provided a restrained approach for SPS development by using a mobile laboratory-based learning model in developing SPS and motivation. A lot of research on addressing SPS through distance learning emphasizes the use of technology, incorporating a laboratory approach, yet not all schools have the privilege of having access to modern technological breakthroughs and advancements.…”
Section: Literature Reviewmentioning
confidence: 99%